Using intuitive awakening for business students to enhance strategic thinking skills - Prince, Melvin; Priporas, Constantinos (Australasian Marketing Journal (AMJ), 2018)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/028-466-664-601-02X, pop00274, princeUsingIntuitiveAwakening2018a tex.type: [object Object]
Keywords: dept.mkt; peer-reviewed

Uniting theory and empirical research: market sensing and marketing research - Prince, Melvin; Gabay, G; Priporas, Constantinos; Moskowitz, H (Quantitative research methods in consumer psychology: contemporary and data driven approaches, 2018)
Quantitative consumer research has long been the backbone of consumer psychology producing insights with peerless validity and reliability. This new book addresses a broad range of approaches to consumer psychology research along with developments in quantitative consumer research. Experts in their respective fields offer a perspective into this rapidly changing discipline of quantitative consumer research. The book focuses on new techniques as well as adaptations of traditional approaches and addresses ethics that relate to contemporary research approaches. The text is appropriate for use with university students at all academic levels. Each chapter provides both a theoretical grounding in its topic area and offers applied examples of the use of the approach in consumer settings. Exercises are provided at the end of each chapter to test student learning. Topics covered are quantitative research techniques, measurement theory and psychological scaling, mapping sentences for planning and managing research, using qualitative research to elucidate quantitative research findings, big data and its visualization, extracting insights from online data, modeling the consumer, social media and digital market analysis, connectionist modeling of consumer choice, market sensing and marketing research, preparing data for analysis;, and ethics. The book may be used on its own as a textbook and may also be used as a supplementary text in quantitative research courses.
Keywords: dept.mkt